Penggunaan Model Pembelajaran Kooperatif Tipe SAVI Untuk Meningkatkan Aktivitas Dan Hasil Belajar Geografi - Noviyani Noviyani; Sumadi Sumadi; Zulkarnain Zulkarnain (JPG (Jurnal Penelitian Geografi), 2018)
The problem this research was motivated by the low learning results on Geography and also the limited application of learning model especially for types like SAVI. This research aims to find out: 1) the improvement on students' learning activity by using SAVI learning model; 2) the improvement on students' learning results by using SAVI learning model on Geography The method used in this research was classroom action research with all. The results of this research showed that; 1) there was an improvement on students' learning activity after being taught with SAVI learning model; the students more active in the learning process after the application of SAVI learning model; 2) there was an improvement on students' learning results after being taught with SAVI learning model on scores after the application of SAVI model; 3) SAVI learning model is suitable to be applied in grade because it could improve students' learning activity and students' learning results.Masalah penelitian ini adalah rendahnya hasil belajar geografi siswa serta guru masih jarang menggunakan model pembelajaran terutama model pembelajaran tipe Somatik, Auditori, Visual, dan Intelektual (SAVI). Penelitian ini bertujuan untuk mengetahui: 1) untuk mengetahui peningkatan aktivitas belajar siswa  dengan penggunaan model pembelajaran SAVI pada mata pelajaran geografi kelas 12 IPS 1; 2) untuk mengetahui peningkatan hasil belajar siswa dengan penggunaan model pembelajaran SAVI pada mata pelajaran geografi kelas. Metode yang digunakan dalam penelitian ini adalah penelitian tindakan kelas. Hasil penelitian ini menunjukkan; 1) terdapat peningkatan aktivitas belajar siswa setelah diterapkan model SAVI siswa cenderung lebih aktif dalam proses pembelajaran; 2) terdapat peningkatan hasil belajar siswa setelah diterapkan model SAVI sebagian siswa memperoleh nilai diatas KKM; 3) Model Pembelajaran SAVI cocok diterapkan di kelas karena dapat meningkatkan aktivitas belajar dan hasil belajar siswa mata pelajaran geografi. Kata kunci: aktivitas, hasil belajar, SAVI